A global overview of the trophic structure within microbiomes across ecosystems. (June 2021) - Xiong, Wu; Jousset, Alexandre; Li, Rong; Delgado-Baquerizo, Manuel; Bahram, Mohammad; Logares, Ramiro; Wilden, Benjamin; de Groot, Gerard Arjen; Amacker, Nathalie; Kowalchuk, George A.; Shen, Qirong; Geisen, Stefan
Highlights: We investigated paired bacteria and protists across ecosystems at the global scale. Predatory protists dominated in soils, phototrophs dominated in aquatic environments. Predatory protists positively correlated with bacterial richness in natural soils. Anthropogenic factors might have negative effects on microbiome trophic structures. Abstract: The colossal project of mapping the microbiome on Earth is rapidly advancing, with a focus on individual microbial groups. However, a global assessment of the associations between predatory protists and their bacterial prey is still missing at a cross-ecosystem level. This knowledge is critical to better understand the importance of top-down links in structuring microbiomes. Here, we examined 38 sequence-based datasets of paired bacterial and protistan taxa, covering 3, 178 samples from diverse habitats including freshwater, marine and soils. We show that community profiles of protists and bacteria strongly correlated across and within habitats, with trophic microbiome structures fundamentally differing across habitats. Soils hosted the most heterogenous and diverse microbiomes. Protist communities were dominated by predators in soils and phototrophs in aquatic environments. This led to changes in the ratio of total protists to bacteria richness, which was highest in marine, while that of predatory protists to bacteria was highest in soils. Taxon richness and relative abundance of predatory protists positively correlated with bacterial richness in marine habitats. These links differed between soils, predatory protist richness and the relative abundance of predatory protists positively correlated with bacterial richness in forest and grassland soils, but not in agricultural soils. Our results suggested that anthropogenic pressure affects higher trophic levels more than lower ones leading to a decoupled trophic structure in microbiomes. Together, our cumulative overview of microbiome patterns of bacteria and protists at the global scale revealed major patterns and differences of the trophic structure of microbiomes across Earth's habitats, and show that anthropogenic factors might have negative effects on the trophic structure within microbiomes. Furthermore, the increased impact of anthropogenic factors on especially higher trophic levels suggests that often-observed reduced ecosystem functions in anthropogenic systems might be partly attributed to a reduction of trophic complexity.